(untitled) (Veterinary Science, 2019)
Dirofilaria Immitis is a zoonotic parasitosis produced by a nematode responsible for generating, in infected animals, potentially fatal cardiopulmonary disease. The dirofilariosis occurs in warm areas, with moisture, beeing the mosquito the vector responsible for its transmission. Despite its denomination, it is a mainly pulmonary disease, affecting the cardiac part in advanced stages. It has different larval stages, but stage L3 is infectious. It enters the host through the vector bite and begins to develop to adult stages which are located at the pulmonary arteries. The main definitive host and reservoir is the dog, but it can affect other wild canids like the fox. The clinical signs range from exercise intolerance, coughing, respiratory crackles and as the parasitic load progresses and increases, hemoptysis or epistaxis, weight loss, syncopes, may occur. In order to arrive at its diagnosis, the detection of microfilariae is essential, whether by taking blood smears from microhematocrit tubes or by the Knott test. Its treatment consists in, the elimination of the young filariae by the administration of macrocyclic lactones and then the use of an adulticide drug, melarsomine diclohydrate. The climatic changes that have occurred in the last time are of concern due to their propagation towards the north of Patagonia, and particularly to our province of La Pampa.